Accommodating Poverty
XVI, 292 p.
Keywords: This book offers a detailed examination of the living arrangements and material circumstances of the poor betweeen 1650 and 1850. Chapters investigate poor households in urban, rural and metropolitan contexts, and contribute to wider investigations into British economic and social conditions in the long Eighteenth century.